School dropouts in Spain: A systematic review - Berral-Ortiz, Blanca; Ramos-Navas-Parejo, Magdalena; Lara-Lara, Fernando; Moreno-Palma, Natalia (Frontiers in Education, 2022)
Dropout is a phenomenon that is unfortunately occurring worldwide and is of increasing concern to authorities. It is a reality that quality indicators in many models are affected by the number of students who drop out of school at higher levels. However, this is not only reflected at the educational level, but also affects the social and personal development of young people. The analysis of school dropout among young Spaniards is a topic of interest due to the repercussions it generates in social, personal and institutional spheres. The objectives of this study were to analyse how many studies have been published on the subject since 2010, locating the selected articles in areas of knowledge and studying the institutions where the research has been carried out. On the other hand, it has been observed how many studies have been focused on the search for the reasons that lead to high dropout rates and the main factors. Finally, an attempt has been made to analyse how many of them are aimed at solving the problem and preventing early school leaving in primary education in order to avoid drop-out at higher levels, by examining the proposals established to reduce the problem. In order to achieve the proposed objectives, a systematic review was carried out with the aim of carrying out a rigorous analysis of the existing and relevant scientific literature on the subject. After applying various exclusion and inclusion criteria, eliminating duplicate records and analysing the works in depth, 28 articles were selected. The results suggest that, currently, despite the problems caused by early school leaving, it is not a subject that has been widely studied and that the main causes are due to educational and social reasons. In the same context, of the articles selected, only 12 present different proposals for the prevention of early school leaving. In the light of the above, it is necessary to look more deeply into the nature of early school leaving in Spanish institutions.